Binary Logistic Regression Model of Parental Interest in Islamic Boarding Schools with R Program: A Case Study Islamic Boarding Schools Tahfidz Daarul Qur'an Tangerang - Sastro, Gerry; Syafiih, Abdullah; Ilmadi (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2024)
This paper aimed to determine factors that affect significantly of parental interest in Islamic Boarding Schools. The subjects of the study were parents of students at Tahfidz Daarul Quran, an Islamic boarding school in Tangerang. A binary logistic regression model was used to analyze the association between parental interest and some covariates namely volition, needs, motivation, knowledge and school environment with used software R. The results showed that a binary logistic model combining knowledge and school environment provides the best model as the significance values of 5.02e-05 and 1.53e-04 are still 0.05 smaller and the wald values are 16.440 and 14.335 which are greater than 3,841. The coefficient estimation of the knowledge variable is 0.246 with an odds-ratio value exp (0.246) = 1.27. This means that parents who have a knowledge of Islamic boarding schools of 1.27 times more interested than do not have knowledge. Furthermore, the coefficient estimation of the school environment is 0.234 with an odds ratio value exp (0.234) = 1.26. It means that parents are more interested 1.26 times in a good school environment than in a bad school environment. So, knowledge and school environment are factors that greatly influence parents' concerns when choosing an Islamic boarding school.